Вивчення народного (говіркового) мовлення в позакласній роботі ЗЗСО - Руснак, Наталія Олександрівна; Струк, Іванна Михайлівна; Руснак, Юлія Маноліївна (Чернівці–Сучава: БДМУ, 2022)
The studying of folk (dialectal) speech is important in the school course of the Ukrainian language, especially in rural areas, as it offers an understanding of the specificity of the Ukrainian language in its territorial expression. Awareness of the specificity of the territorial variety of the Ukrainian language will contribute to the manifestation of patriotic feelings of students, the desire to preserve the ethnic (territorial) peculiarity. The relevance of our research is determined by the need to study folk speech in the school course of the Ukrainian language. The purpose of the article is to develop the topics of one of the forms of extracurricular work (of a colloquium) on the Ukrainian language for the study of spoken language in secondary school. The research was carried out on the material of the dialects of the villages of Ulashkivtsi and Zabolotivka of the Chortkiv district of the Ternopil region. Research methods. The research was carried out on the main general scientific methods of analysis and synthesis, as well as on linguistic methods – descriptive, structural. With the help of the descriptive method the factual material was summarized. The inventory and systematization of language phenomena was promoted by the structural method. Conclusions. As a result of the insufficient coverage of information from the "Dialectology of the Ukrainian language" in school teaching course of the Ukrainian language, the role of extracurricular work as one of the types of educational work is increasing, the purpose of which is to deepen the information from this course, as well as to explain to schoolchildren the differences between folk (colloquial) words and literal names. Therefore, students must understand the specifics of the manifestation of the territorial variety of the national Ukrainian language. For this purpose, the most optimal form of extracurricular work is a colloquium, during which the teacher will provide information about the types of dialectal phenomena, tell about the origin of the dialecticisms of speech, offer information about the vocabulary of the calendar cycle (middle grades), and explain the phonetic-grammatical regularities of dialectal speech (senior grades)
Studying of folk (dialectal) speech in extracurricular work of middle school
Keywords: folk dialectal speech; literal names; extracurricular work; middle school; the Ukrainian language